Mastication as a tool to prevent cognitive dysfunctions - Gayathri Krishnamoorthy; Aparna I. Narayana; Dhanasekar Balkrishanan (Elsevier, 2018)
Summary: Mastication as we all know has always been related to its primary function of digestion, but little do we know that it produces an enhancing effect on general health, especially the cognitive performance related aspects of memory. Recent studies have shown its association with activation of various brain regions, however little is known about its effects on neuronal activity in these specified regions. According to the enormous evidences collected so far, mastication has proved to be effective in conducting huge amount of sensory information to the brain, and maintaining learning and memory functions of hippocampus. Therefore it is essential that we maintain normal occlusion and preserve the masticatory function as long as possible to prevent the attenuation of hippocampus, caused by occlusal disharmony and reduced mastication. We provide an overview on how mastication activates various cortical areas of the brain and how an increase in the cerebral blood oxygen level of hippocampus and prefrontal cortex (PFC) accentuates the learning and memory process. We also justify why maintaining and establishing a normal occlusion is important from neurological point of view. Keywords: Mastication, Brain functions, Stress, Occlusion, Occlusal disharmony